The development of reading comprehension and writing skills in English learning - Calderón Bueno, Leidy Alexandra; Rey Suárez, Dary Jazmín (Rastros Rostros, 2012)
This paper presents the advances of the research project “English teaching as a second language based on icts”, developed at the Escuela Normal Superior de Bucaramanga: this research began on the second semester of 2010. After watching the students in their English classes and then applying a survey to the same group of students, we saw in the results great shortcomings in reading comprehension and writtenproduction. We also present here the results of the planning and execution processes of this research, that seeks to foster teaching strategies for English language reading comprehension and written production through the use of icts in the classroom
Keywords: classroom; reading; didactics; writing